Assessment of Canine Autologous Conditioned PlasmaTM Cellular and Transforming Growth Factor-β1 Content - Franklin, Samuel P.; Birdwhistell, Kate E. (Frontiers in Veterinary Science, 2018)
Objectives: To evaluate 1) the cellular composition of canine ACP™ including using two different preparation protocols with variations on centrifugation time, 2) the effect of different activation protocols on the transforming growth factor (TGF)-β1 content in the ACP, and 3) patient factors that might influence platelet concentration of the ACP. Methods: ACP was made with blood from 15 dogs using a manufacturer-recommended protocola. Each ACP sample was divided into three aliquots that were activated with calcium chloride (CaCl2), human γ-thrombin (HGT), or not activated. TGF-β1 was quantified in each aliquot using an ELISA and comparisons among activation protocols were performed using a Skillings-Mack test. Correlations between platelet and TGF-β1 concentration were assessed with a Pearson correlation coefficient. ACP was subsequently prepared from an additional 17 dogs using a slightly modified centrifugation protocol and cellular composition was assessed. Effects of dog age, body weight, and hematocrit were assessed for their potential impact on ACP platelet concentration using a multiple linear regression analysis. Results: The mean increase in platelet concentration in the ACP above that in the whole blood was 1.2X (±std 0.62) and leukocyte concentration was a mean of 26% that in the whole blood (0.37) using the standard protocol. There was a significant (p<0.01) effect of activation on TGF-β1 concentrations with mean concentrations of 4,538 (2,317), 14,948 (13,784), and 14,096 pg/ml (15,210) in aliquots that were not activated or were activated with thrombin or CaCl2 respectively. There were significant correlations between the platelet concentration and TGF-β1 concentration in aliquots that were activated with either thrombin (r=0.66; p<0.01) or CaCl2 (r= 0.86, p<0.0001). The mean increase in platelet concentration was 1.4x (0.62) and the leukocyte concentration was 0.28x (0.13) that in whole blood using the modified ACP preparation protocol. Dog age, body weight, and hematocrit were not significant predictors of ACP platelet concentration. Conclusions: These data show that on average this preparation protocol produces a mildly platelet-concentrated, leukoreduced platelet-rich plasma. Intentional activation had a significant effect on TGF-β1 concentrations with use of both CaCl2 and thrombin resulting in higher TGF-β1 concentrations than that obtained in samples that are not activated.